161 Dietary oxidized protein result in growth and histology differences in pigs - Frame, Carl A (J Anim Sci, 2020)
Rendered by-products are common feedstuffs in diets. During processing, these sources have potential to become oxidized. While most research on oxidative stress has focused on dietary oxidized lipids, little research has been done in dietary oxidized proteins and the potential to induce oxidative stress. Recent studies have shown consumption of dietary oxidized proteins resulted in shifts in oxidative status. The objective of this study was to determine the effects of dietary oxidized protein on oxidative stress in pigs as a model for canines. Fifty-six, 3 weeks old pigs (5.55 ± 0.71 Kg) were fed 4 dietary treatments each varying in dietary oxidized protein. Each treatment was fed the same diet, with the exception of the degree of oxidation in chicken by-product meal which was included in the diet at 23 percent to represent typical inclusion levels of a companion animal diet. Oxidation was induced by 2 levels of heating and 2 levels of antioxidants (mixed tocopherol), in a 2 x 2 factorial design. A significant antioxidant effect was observed in villi height (P-value < 0.05) where pigs fed diets without antioxidant had increased villi height (674 μm) compared to those fed diets with antioxidants (576 μm). Additionally, pigs fed diets without antioxidant had significantly greater villi:crypt (3.22) compared to those fed diets with antioxidants (2.84 ; P-value < 0.05). Additionally, feed efficiency measured by gain:feed, was significantly decreased in pigs fed heated protein (0.65) compared to not heated (0.69; P-value < 0.05). Results from this study are consistent with previous studies (Dibner, et al., 1996). Future studies should examine the effects of feeding oxidized proteins in regard to oxidative status, such as markers of protein, lipid, DNA, and antioxidative enzyme damage. In conclusion, dietary oxidized protein can reduce feed efficiency in pigs.